2017
DOI: 10.1111/vru.12500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of T2‐weighted versus short‐tau inversion recovery sagittal sequences in the identification and localization of canine intervertebral disc extrusion with low‐field magnetic resonance imaging

Abstract: Sagittal T2-weighted sequences (T2-SAG) are the foundation of spinal protocols when screening for the presence of intervertebral disc extrusion. We often utilize sagittal short-tau inversion recovery sequences (STIR-SAG) as an adjunctive screening series, and experience suggests that this combined approach provides superior detection rates. We hypothesized that STIR-SAG would provide higher sensitivity than T2-SAG in the identification and localization of intervertebral disc extrusion. We further hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Limitations of MRI include prolonged acquisition time, 29,30 availability, and cost 31 . Standard protocols always include T2‐weighted (T2W) images and can be abbreviated to focus on sagittal sequences, 32‐34 but diagnostic accuracy suffers without transverse images 32 . The HASTE/T2* or short Tau inversion recovery (STIR) sequences might complement T2W images, 34,35 whereas inclusion of post‐contrast imaging does not improve diagnostic accuracy or treatment planning in most cases 36,37 .…”
Section: Diagnostic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of MRI include prolonged acquisition time, 29,30 availability, and cost 31 . Standard protocols always include T2‐weighted (T2W) images and can be abbreviated to focus on sagittal sequences, 32‐34 but diagnostic accuracy suffers without transverse images 32 . The HASTE/T2* or short Tau inversion recovery (STIR) sequences might complement T2W images, 34,35 whereas inclusion of post‐contrast imaging does not improve diagnostic accuracy or treatment planning in most cases 36,37 .…”
Section: Diagnostic Approachesmentioning
confidence: 99%
“…Standard protocols always include T2‐weighted (T2W) images and can be abbreviated to focus on sagittal sequences, 32‐34 but diagnostic accuracy suffers without transverse images 32 . The HASTE/T2* or short Tau inversion recovery (STIR) sequences might complement T2W images, 34,35 whereas inclusion of post‐contrast imaging does not improve diagnostic accuracy or treatment planning in most cases 36,37 . It remains to be determined if half‐Fourier acquisition single‐shot turbo spin‐echo (HASTE) is complementary or additive to T2W images or only worthwhile if the T2W images do not show evidence of hyperintensity.…”
Section: Diagnostic Approachesmentioning
confidence: 99%
“…Ultrafast heavily T2W, short T1 inversion recovery (STIR), and gradient echo sequences (GRE, also known as T2 * or fast field echo-FFE) are also routinely acquired (Figure 4). A low-field MRI study looked at sagittal STIR images compared to sagittal T2W and found no difference (81). However, the parallel evaluation of the paired sagittal T2W and STIR series yielded a higher sensitivity than using either sagittal screening series in isolation (81).…”
Section: Image Sequencesmentioning
confidence: 99%
“…A low-field MRI study looked at sagittal STIR images compared to sagittal T2W and found no difference (81). However, the parallel evaluation of the paired sagittal T2W and STIR series yielded a higher sensitivity than using either sagittal screening series in isolation (81). Heavily T2W images, also called "myelo-MRI" or HASTE (Half-Fourier acquisition single-shot turbo spin echo) images, can be used to highlight the cerebrospinal fluid signal and rapidly identify an area of interest (Figure 4).…”
Section: Image Sequencesmentioning
confidence: 99%
“…By highlighting the dorsal and ventral cerebrospinal fluid (CSF) columns these sequences are useful for rapidly identifying regions of interest. Two studies have shown that they are not as reliable as T2W sagittal images for identifying the site of compression (Guillem Gallach et al., 2011 ; Housley et al., 2017 ) but are useful to highlight spinal cord swelling, and the suggestion is this may be a useful predictor of progressive ascending‐descending myelomalacia (Gilmour et al., 2017 ; da Costa et al., 2020 ). Using a similar technique, we hypothesised it may be possible to use HASTE sequences to correlate CSF attenuation and clinical severity at presentation.…”
Section: Introductionmentioning
confidence: 99%